Socio‐ecological and economic aspects of tropical tuna fisheries in the Mozambique Channel. (16th November 2021) - Nataniel, Anildo; Lopes, Priscila F. M.; Lopez, Jon; Soto, Maria
Abstract: Industrial and small‐scale tuna fisheries in Mozambique may compete over the same resources, which has potential socio‐ecological impacts. The two types of fisheries were investigated by characterising their catch trends, types of interactions, number of people they employ and revenues. Commercial landings, logbook data and all previously established tuna Fishing Partner Agreements in the country were analysed, as well as data collected from interviews with small‐scale fishers. A declining trend in catches was observed in the industrial fisheries sector, which was also perceived by small‐scale fishers, and suggests that there is some competition between these two sectors for the same tuna stocks, even when these stocks are targeted in separate grounds. While the small‐scale tuna fisheries sector provides thousands of local direct and indirect jobs and high economic benefits for fishing communities, the industrial fisheries sector may only be economically advantageous to Mozambique if Fishing Partner Agreements are improved and enforced. Although maintaining non‐overlapping fishing grounds between industrial and small‐scale fisheries may be positive for the fishers, it could result in major pressure on the tuna stocks, as they would be exploited relentlessly.